ANALISIS SIKAP KONSUMEN PADA ATRIBUT PRODUK PONSEL CINA DI PEKANBARU - Sulistyowati, Lilis; ', Hermawan; ', Jushermi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study held in Pekanbaru in order to analyze consumer’s attitude on product attributes of China celuller. Population are China celuller users in Pekanbaru. Sampling technique accidental sampling is done using the number of respondests 96 people. Data analyzed by using Fishbein Multi Attribute Analysis. This study reveals that most respondents have a negative attitude towards China celuller attributes. The three most positive attitude come from design, packaging and brand. Meanwhile, the three most negative ones are label, features and quality. It is recommended to provide a more clear and comprehenable language in manual instruction book, internally installing additional features to the handset, enhancing the LED and battery quality, expanding internal memory capacity and informing the term and conditions in external application process.Keywords: Attitude, Product Attributes, and Believe